The roles of attachment styles and emotional intelligence in predicting decision-making skills in a secondary school in Negeri Sembilan - Sharif, Nurul Nuraeen; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This study aims to examine the relationships between attachment styles in predicting decision-making skills and emotional intelligence of a total 181 form 4 students in a secondary school located at Negeri Sembilan. The instrument used was adapted from Schutte et.al., (1998), Bakker et al., (2004) and Mincemoyer & Perkins (2003). The study employs a descriptive-correlational design. Exploratory data analyses were performed to obtain descriptive data from the sample. ANOVA analysis was conducted to determine whether there are significant differences between attachment styles and emotional intelligence and also between attachment styles and decision-making skills among subjects. Pearson correlations were employed to determine whether there are any significant relationships between emotional intelligence and decision-making skills among the subjects. The result of this study shows that there is a positive association between emotional intelligence and decision-making skills among secondary school students.